How to keep well in wartime - Great Britain. Ministry of Health ; Central Council for Health Education (Great Britain); Clegg, Hugh Anthony, 1900- (London : His Majesty's Stationery Office, 1943)
1943 1943 1940s 28 pages : illustrations CHOOSE THE RIGHT FOOD to understand why Lord Woolton has taken the doctors' advice to increase the cheese ration and add calcium to flour. Vitamins Protect You. Just as calcium and iron are present in sufficient amount in a well-mixed ample diet, so are the vitamins. It is a pity vitamins are labelled with the letters of the alphabet. It makes them seem unreal and mysterious. But they are real enough, being rather complicated chemical substances made up of carbon, hydrogen, oxygen, nitrogen, and sulphur, especially of the first three of these. The chemist can now manufacture some of them in his laboratory — Vitamin C for example. We need very small amounts of the vitamins, and only very small amounts of them exist in foodstuffs. But without vitamins the fuel — sugars and fats — in your body will be wasted. They will burn badly and there will be a lot of smoke. Vitamin A, for example, protects the eyes. Vitamin B keeps the skin clear and the nerves steady. Vitamin C saves you from scurvy, and Vitamin D from rickets. Vitamin E helps you to be fertile, and Vitamin K stops you from bleeding when you shouldn't. No wonder doctors call foods rich in vitamins "protective" foods. Now all these and other vitamins are present in natural foods and always have been. Unfortunately, it has not always been possible for people to eat the right kind of foods, or they have been ignorant of what to eat. What you fancy does not necessarily do you good. How to Get Your Vitamins. Eat as much as you can of the protective foods. You buy these at the greengrocer's, the dairy, and the fish shop. Milk, butter, cheese and eggs are available in varying and restricted amounts. So be sure each member of the family has his or her full ration of them, and see that the children get the extra ration of milk the Government provides to meet their special needs. The same applies to the expectant mother. The manufacturers add the "sunshine vitamins" A and D to margarine, so this can be classed as a dairy food. Cheese is a useful food for children, and cooking doesn't take away its goodness. Vitamin D is not found in many foods, though there is some in fat fish (like herring and salmon), so unless fish-liver oils are taken we have to depend for Vitamin D largely on the action of sunlight on the skin. Therefore full advantage should be taken of the cod-liver oil obtainable from the Welfare Centres for expectant mothers and children under five. Eat fish when you can, especially fat fish, and especially herrings. How to Replace the Vitamin in Oranges. Now that foreign fruits like oranges are, to say the least of it, scarce, you must make the most of what there is at home. Oranges and lemons were valuable chiefly because of the Vitamin C in them. There is a lot of Vitamin C in the good old-fashioned " two veg.", potatoes and cabbage; and in tomatoes, watercress, parsley, broccoli, and swede turnip. If 11 420/BS/7/16/18